Koncept trajnostno kompaktnega mesta - Šulin Košar, Anja (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2014)
The compact city concept has emerged at the end of the 20th century as one of the solutions for sustainable urban development. The concept brings development, which emphasizes urban density, while avoiding urban sprawl. The key features of the concept are mixed land use, construction of higher density (city intensification) as well as better access for the entire population and most importantly, development of the public transport system. The concept has advantages, but also disadvantages, because too much density affects the quality of life in the city.
Keywords: environmental protection; kvaliteta življenja; Ljubljana; mesta; Slovenia; Slovenija; sustainable development; trajnostni razvoj; urbana geografija; varstvo okolja